2023
DOI: 10.25646/11144
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for collecting and analysing migration-related determinants in public health research

Abstract: Background According to the definition of the German Federal Statistical Office, about every fourth person living in Germany has a so-called migration background (MB), i.e., the person or at least one of their parents was born without German citizenship. However, MB has been defined differently in many studies. Also, the MB summarises people in different living situations, making differentiated analysis in health science more difficult. This article formulates recommendations for the collection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“…Brydsten et al [14] found that experiences of discrimination were an explanatory factor regarding the mental health gap especially for non-European migrants. Additional relevant migration-related indicators have recently been proposed for future research on migration and health in Germany, including reasons for migration, self-reported discrimination, social support and sense of belonging to society [24]. Therefore, the neglect of subjective experiences of discrimination and racism remains a blind spot in the NAKO study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brydsten et al [14] found that experiences of discrimination were an explanatory factor regarding the mental health gap especially for non-European migrants. Additional relevant migration-related indicators have recently been proposed for future research on migration and health in Germany, including reasons for migration, self-reported discrimination, social support and sense of belonging to society [24]. Therefore, the neglect of subjective experiences of discrimination and racism remains a blind spot in the NAKO study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…People with migration background are not a homogenous group but instead consist of a broad range of nationalities, cultures, origins, languages, experiences and socioeconomic determinants [23,24]. The concept and definition of migration background in Germany has been described in detail by Will [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alle Menschen haben aus menschenrechtlicher Sicht dasselbe Recht auf medizinische Versorgung und bestmögliche Gesundheit [9]. Aus diesem zunächst abstrakten Recht auf Gesundheit ergeben sich konkrete, operationalisierbare Maßnahmen und Rahmenbedingungen für Gesundheitssysteme [10], die die Gesundheit aller in einem Land lebenden Menschen adressieren und nicht aussen die Migrationserfahrung strukturierende biografische, soziale, migrationsbezogene und strukturelle Faktoren separat zu erheben [8]. Im Folgenden sprechen wir von Personen mit eigener oder familiärer Migrationsgeschichte,um auf Personen zu verweisen, deren Biografie durch Migrationserfahrung mitgeprägt ist.…”
Section: Gesundheitssystem Und Ausbildungsbedarfunclassified
“…"Immigration" itself has been introduced as social determinant of health [42]. In practice this category gets broken down into ever more internal distinctions, but the (super-)diversity [43,44] of migrant populations is barely reflected in statistical categories, calling for a more nuanced approach of considering differences by legal status and other characteristics [45]. Societies differentiate "types of migrants [.…”
Section: Introductionmentioning
confidence: 99%